2023
DOI: 10.1002/adom.202300618
|View full text |Cite
|
Sign up to set email alerts
|

Redox‐Modulated Circularly Polarized Luminescence in Chiral Photonic Films Derived from Cellulose Nanocrystals and Polyoxometalate

Abstract: Achieving smart circularly polarized luminescence (CPL) materials with large luminescence dissymmetry factor (glum) is in high demand for potential technological applications in the chiroptical fields. Herein, a series of chiral photonic crystals (CPCs) derived from cellulose nanocrystals (CNCs) and photosensitive inorganic polyoxometalates (POMs) through an evaporation‐induced self‐assembly strategy are reported. The photonic bandgaps (PBGs) of CPC films are well regulated by controlling the amount of doped P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Chiroptical difference through (b 8 ) an L-CP and (b 11 ) an R-CP. Reproduced with permission from ref . Copyright 2016 Wiley-VCH.…”
Section: Photonic Materials Based On Cellulose Nanocomposite Filmsto...mentioning
confidence: 99%
See 1 more Smart Citation
“…Chiroptical difference through (b 8 ) an L-CP and (b 11 ) an R-CP. Reproduced with permission from ref . Copyright 2016 Wiley-VCH.…”
Section: Photonic Materials Based On Cellulose Nanocomposite Filmsto...mentioning
confidence: 99%
“…Beside the nanoparticles, inorganic materials are also a practical candidate for creating nanocellulose composite films. Zhang et al 112 evaluate the circularly polarized luminescence of an inorganic polyoxometalates/CNCs composite film (Figure 10b). They confirmed that the photonic bandgaps of the composite films can be well regulated by controlling the amount of polyoxometalate filler, yielding tunable right-handed circularly polarized luminescence emission with tailored dissymmetry factor.…”
Section: Photonic Materials Based On Cellulose Nanocomposite Films�to...mentioning
confidence: 99%
“…10–15 This can be achieved by various external stimuli such as temperature, 16 solvents, 17 light, 18 metal ions, 19 pH, 20 and redox. 21 However, most of the reported supramolecular chirality inversions have focused on single-component self-assembled systems, 22–25 and both basic and application research studies of multiple-component co-assemblies with controllable chirality are still limited. The study of supramolecular chirality inversion in multicomponent systems not only benefits simulation of complicated biosystems, but also provides considerable meaning to the rational design and manufacture of advanced chiroptical materials.…”
Section: Introductionmentioning
confidence: 99%